2010
DOI: 10.1097/fbp.0b013e32833aec4d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2-AG on the reinforcing properties of wheel activity in obese and lean Zucker rats

Abstract: The endocannabinoid system plays a role in obesity, primarily by its role in food reward. Activity, also involved in obesity, seems to be at least partially controlled by the endocannabinoid system, but the relevant behavioral and neurochemical mechanisms have not been well established. This study represents an attempt to begin elucidating these mechanisms by examining the effects of an endogenous cannabinoid ligand, 2-arachidonoylglycerol (2-AG), on the reinforcing properties of exercise reinforcement in lean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 60 publications
(82 reference statements)
1
21
0
Order By: Relevance
“…Evidence of diaphragm weakness and atrophy in the absence of in vitro functional impairment. We chose to investigate the function and morphology of the diaphragm, a constitutively active muscle to remove disuse atrophy as a potential confounding variable as, while physical activity has not been specifically investigated in the ZDF strain, previous studies have identified that the obese Zucker strain has decreased spontaneous activity and wheel activity, compared with lean controls (38,39). Functional analysis of the diaphragm revealed that baseline esophageal pressures were not different between ZDF and lean controls during eupneic breathing (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Evidence of diaphragm weakness and atrophy in the absence of in vitro functional impairment. We chose to investigate the function and morphology of the diaphragm, a constitutively active muscle to remove disuse atrophy as a potential confounding variable as, while physical activity has not been specifically investigated in the ZDF strain, previous studies have identified that the obese Zucker strain has decreased spontaneous activity and wheel activity, compared with lean controls (38,39). Functional analysis of the diaphragm revealed that baseline esophageal pressures were not different between ZDF and lean controls during eupneic breathing (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, eCB regulation of exercise may be related to metabolic status as the motivation for wheel running, and the wheel-running behavior itself, is differentially responsive to cannabinoid ligands in lean compared to obese Zucker rats (Smith and Rasmussen, 2010). Taken together, the apparent role for the hippocampus in energy management, coupled with the robust effect of exercise on hippocampal structure and function, indicate that the influence of wheel running on the hippocampus should not be discounted in studies of food intake and energy expenditure.…”
Section: Behavioral Aspects Of Wheel Running: Wheel Running Influementioning
confidence: 99%
“…It is possible that obese rats’ behavior was insensitive to the effects of rimonabant because of their genotype, though this is unlikely as rimonabant effects were observed in the reinforcer and response data. Moreover, a number of studies show that obese Zucker rats are especially sensitive to CB 1 compounds (Rasmussen and Huskinson 2008; Smith and Rasmussen 2010; Vickers et al 2003). It is more likely that while rimonabant reduced behavior and reinforcers earned overall across all schedules of the obese Zucker rats, the allocation of behavior did not change due to rimonabant.…”
Section: Discussionmentioning
confidence: 99%
“…After this point, access to food was restricted to a daily 2-hr free-feeding session immediately following experimental sessions; this established food as a reinforcer. This restriction procedure results in both lean and obese Zucker rats consuming 2.3–2.6% of their body weight in food (Rasmussen et al 2010; Rasmussen and Huskinson 2008; Smith and Rasmussen 2010). This also allows deprivation levels to be held constant between lean and obese rats and prevents rapid weight gain, which is linked to health problems in the obese Zucker rat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation